2008
DOI: 10.1016/j.jacc.2007.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted Clopidogrel Loading Doses According to Vasodilator-Stimulated Phosphoprotein Phosphorylation Index Decrease Rate of Major Adverse Cardiovascular Events in Patients With Clopidogrel Resistance

Abstract: This is the first study to suggest that adjusting the clopidogrel loading dose according to platelet monitoring using the VASP index is safe and may significantly improve the clinical outcome after PCI in patients with clopidogrel resistance despite a first 600-mg loading dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
332
1
16

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 534 publications
(358 citation statements)
references
References 30 publications
7
332
1
16
Order By: Relevance
“…This indicates that the VASP-P assay is insensitive to low levels of P2Y 12 -blockade (46) and might in part explain the poor specificity of the assay, which limits its value for guiding individual therapy. Small randomised controlled trials have recently shown that tailoring clopidogrel LD in non-emergent patients based on a PRI cut-off of 50% significantly improves the patients' outcome (22,23). Translating these results to our data, 62% of patients would require reloading or a change in thienopyridine therapy.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This indicates that the VASP-P assay is insensitive to low levels of P2Y 12 -blockade (46) and might in part explain the poor specificity of the assay, which limits its value for guiding individual therapy. Small randomised controlled trials have recently shown that tailoring clopidogrel LD in non-emergent patients based on a PRI cut-off of 50% significantly improves the patients' outcome (22,23). Translating these results to our data, 62% of patients would require reloading or a change in thienopyridine therapy.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, it has been found to be predictive for major adverse cardiovascular events (MACE), including stent thrombosis after PCI and stent implantation (11,21). Recently, small randomised controlled trials have shown that tailoring clopidogrel loading doses (LD) in non-emergent patients based on a platelet reactivity index (PRI) cut-off of 50% significantly improves the patients' outcome (22,23). Taking these data into account, the VASP-P assay, although not a bedside test, might be considered for assessing clopidogrel responsiveness in routine practice.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 In vitro tests of VASP phosphorylation analysis accurately detect biological clopidogrel resistance that is associated with worse outcome after PCI. 33 -35 Bonello et al 21 demonstrated that PRI using VASP monitoring is safe and significantly improves clinical outcome after a 600-mg LD. Furthermore, a tailored 600-mg clopidogrel LD according to PRI also prevents acute and subacute ST in the same patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 -13 Several methods have been developed to deal with clopidogrel resistance, 14 of which the most popular strategy is increasing the loading dose (LD) utilized in patients undergoing PCI to 600 mg 15 -18 and 900 mg. 19,20 Although clopidogrel response is dose-dependent, there is a threshold to its platelet-inhibitory effect when certain doses are administrated. 19,20 In order to find a better method to tackle clopidogrel resistance, Bonello et al 21 adjusted the clopidogrel LD according to platelet monitoring using the vasodilator-stimulated phosphoprotein (VASP) index in a multicenter randomized prospective study, and observed that it was safe and significantly improved the clinical outcomes after PCI in patients with clopidogrel resistance. In another study, Bonello et al 22 also demonstrated that tailoring the clopidogrel LD according to platelet reactivity monitoring decreased the rate of early stent thrombosis (ST) after PCI without increasing bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, considerable interindividual variability exists in response to clopidogrel, and those with high on-clopidogrel platelet reactivity are at increased risk of cardiovascular events. 3,4 Several clinical, genetic, and cellular factors have been suggested as mechanisms for clopidogrel response variability. 5 One of the common causes of individual variations in drug response is genetic polymorphism associated with drug absorption and metabolism.…”
Section: Introductionmentioning
confidence: 99%